A method for preparing a porous copper-zinc alloy current collector, the resulting product and applications

CN122979693APending Publication Date: 2026-10-27SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611178883.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,现有合金化改性工艺仍普遍存在流程复杂、难以精准控制合金组成等不足

Benefits of technology

1. 原料的多样性:该方法适用于多种商业黄铜箔(如H62、H65、H70),无需定制前驱体合金。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979693A_ABST
    Figure CN122979693A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a porous copper-zinc alloy current collector, and the obtained product and application. The preparation method comprises the following steps: taking brass foil as raw material, and combining gas phase dealloying and annealing processes. The gas phase dealloying is used to realize evaporation of excess zinc metal and formation of a porous structure, and the annealing is used to realize uniform diffusion and alloying of a target zinc metal component. The application has the advantages of simple and efficient process, controllable component, strong experimental result repeatability, and low equipment requirement, and is suitable for continuous production of a self-supporting micro-nano porous copper-zinc alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a porous copper-zinc alloy current collector and the resulting product, as well as the application of the product in zinc-ion batteries, specifically as a negative electrode material for zinc-ion batteries, belonging to the fields of porous alloy preparation and zinc-ion battery technology. Background Technology

[0002] With the accelerated global transition to clean energy, safe, efficient, and sustainable large-scale energy storage technologies have increasingly become a focus of attention for both academia and industry. Aqueous zinc-ion batteries, with their inherent safety, abundant zinc resources, high theoretical specific capacity, and environmental friendliness, have shown significant application potential in next-generation energy storage systems. However, their commercialization has been hampered by two major bottlenecks: dendrite growth and corrosion side reactions generated by the zinc metal anode during repeated charge-discharge cycles. On the one hand, uneven zinc deposition easily induces sharp dendrites, whose uncontrolled growth can lead to separator puncture and internal short circuits, seriously threatening battery safety. On the other hand, zinc is thermodynamically unstable in aqueous electrolytes; hydrogen evolution reaction and surface corrosion continuously consume active materials and increase battery polarization, resulting in low coulombic efficiency and severely reduced cycle life. Therefore, developing a zinc anode system that combines high reversibility and long-term stability has become a core issue driving the practical application of aqueous zinc-ion batteries.

[0003] To address the aforementioned bottlenecks, researchers have proposed various modification strategies from the anode side, including constructing artificial interface protective layers, improving current collectors, designing three-dimensional frameworks, and alloying modifications. However, in practical industrial applications, while three-dimensional current collectors and surface coating modifications can regulate zinc deposition behavior to some extent, their preparation processes are lengthy and the raw material and process costs are high, making it difficult to meet the stringent requirements of large-scale production. In contrast, alloying strategies show great potential for large-scale preparation. However, existing alloying modification processes still generally suffer from drawbacks such as complex processes and difficulty in precisely controlling alloy composition. For example, some alloying schemes rely on complex melting-rolling or multi-step chemical treatments, and the uniformity and long-term stability of the introduced alloying elements at grain boundaries are still difficult to guarantee. Therefore, developing a zinc-based alloy material with a simple and efficient process and stable structure and composition is of vital importance for overcoming the stability bottleneck of aqueous zinc-ion batteries under high-rate and long-cycle conditions and promoting their commercialization. Summary of the Invention

[0004] To address the shortcomings of the existing technology, this invention provides a method for preparing a porous copper-zinc alloy current collector. This method is simple, efficient, and has good process stability. The copper-zinc ratio in the obtained porous copper-zinc alloy current collector is stable, which is conducive to large-scale industrial application.

[0005] This invention is achieved through the following means: A method for preparing a porous copper-zinc alloy current collector, the method comprising the following steps: (1) Clean the surface of the brass foil and then vacuum dry it; (2) Place the dried brass foil into a vacuum tube furnace and evacuate it; (3) Introduce a mixture of hydrogen and inert gas into the vacuum tube furnace, then evacuate the vacuum, repeating this process at least once to further remove residual air from the tube. (4) A mixture of hydrogen and inert gas is continuously introduced into the vacuum tube furnace and the furnace is kept at a low pressure. The temperature is raised to carry out vapor phase dealloying treatment. After the treatment is completed, the temperature is lowered to room temperature. (5) Without air entering, a mixture of hydrogen and inert gas is introduced into the vacuum tube furnace until the pressure inside the furnace is atmospheric pressure. Then, the temperature is raised for annealing. After annealing, the temperature is lowered to room temperature to obtain a porous copper-zinc alloy current collector.

[0006] Furthermore, in step (1), the surface of the brass foil is ultrasonically cleaned sequentially using water and anhydrous ethanol.

[0007] Further, in step (1), the brass foil is a commercial brass foil, wherein the mass fraction of copper is 60-70%, for example 60%, 65%, 70%, the mass fraction of zinc is 30-40%, and the thickness of the brass foil is 10-1000 μm, for example 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, 850 μm, 900 μm, 950 μm, 1000 μm.

[0008] Furthermore, in step (2), the brass foil processed in step (1) is placed into a vacuum tube furnace. One end of the vacuum tube furnace is connected to a mixed gas cylinder through an inlet valve, and the other end is connected to a vacuum pump and outside air through a vacuum valve and an outlet valve, respectively. The tube furnace is evacuated by opening the vacuum valve and starting the vacuum pump to evacuate the tube furnace to below 10 Pa in order to remove the air inside the furnace.

[0009] Furthermore, in step (3), the gas inlet valve is opened and a mixture of hydrogen and inert gas is introduced into the tubular furnace. After the gas pressure in the furnace is slightly higher than the normal atmospheric pressure, the gas inlet valve is closed, the gas supply is stopped, and the vacuum valve and vacuum pump are opened again to evacuate the furnace until the pressure inside the furnace is below 10 Pa.

[0010] Furthermore, in step (3), the process of introducing a mixture of hydrogen and inert gas and evacuating the vacuum is repeated 1-3 times.

[0011] Furthermore, in step (4), the gas flow rate is adjusted by the gas inlet valve, and a mixture of hydrogen and inert gas is introduced to maintain the gas pressure inside the furnace at a low pressure. The low pressure state refers to the gas pressure inside the furnace being between 100 and 200 Pa.

[0012] Furthermore, in step (4), the tube furnace is started to perform vapor phase dealloying under the condition of ensuring gas flow and preventing air from entering. The tube furnace settings for the vapor phase dealloying process are as follows: the initial temperature is set to 20-30 ℃, the heating rate is set to 8-11 ℃ / min, the vapor phase dealloying temperature is set to 600-700 ℃, for example 600 ℃, 650 ℃, 700 ℃, and the holding time is set to 2~320 min, for example 2 min, 5 min, 8 min, 10 min, 15 min, 20 min, 25 min, 30 min, 40 min, 45 min, 50 min, 60 min, 70 min, 80 min, 100 min, 150 min, 200 min, 250 min, 300 min, 320 min.

[0013] Furthermore, in step (5), after the vapor-phase dealloyed sample cools to room temperature, the vacuum valve and vacuum pump are closed, and mixed gas is continuously introduced. When the gas pressure inside the pipe is higher than the normal atmospheric pressure, the gas pipe at the outlet valve end is connected to the water tank, and the vent valve is opened to make the gas pressure inside the pipe consistent with the normal atmospheric pressure. Under the condition of ensuring gas flow and preventing air from entering, annealing is carried out at normal pressure. The parameters for the tubular furnace during the annealing process are as follows: initial temperature is set to 20-30 ℃, heating rate is set to 8-11 ℃ / min, annealing temperature is set to 550-650 ℃, for example 550 ℃, 600 ℃, 650 ℃, and holding time is set to 25~360 min, for example 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min, 100 min, 150 min, 200 min, 250 min, 300 min, 360 min.

[0014] Furthermore, in steps (3)-(5) above, the volume fraction of hydrogen in the mixture of hydrogen and inert gas is 5-10%, for example, 5%, 6%, 7%, 8%, 9%, 10%. The inert gas is nitrogen, argon, or other inert gases.

[0015] Furthermore, the porous copper-zinc alloy current collector prepared according to the above method is also within the scope of protection of this invention, wherein the atomic ratio of copper to zinc in the porous copper-zinc alloy current collector is 3:1. The porous copper-zinc alloy current collector has a porous structure with pore sizes of 1-3 μm, which are uniformly distributed on the current collector.

[0016] This invention also provides the application of the aforementioned porous copper-zinc alloy current collector in zinc-ion batteries, preferably aqueous zinc-ion batteries. As a negative electrode material for zinc-ion batteries, the porous copper-zinc alloy current collector of this invention can improve the performance of zinc-ion batteries.

[0017] This invention first uses a vapor-phase dealloying method to obtain a porous copper precursor, and then performs annealing to obtain a porous copper-zinc alloy with a copper:zinc ratio of 3:1. Compared with the prior art, this invention has the following advantages: 1. Diversity of raw materials: This method is applicable to a variety of commercial brass foils (such as H62, H65, H70) without the need for custom precursor alloys.

[0018] 2. Uniqueness of the Process Mechanism: By using vapor-phase dealloying, excess zinc beyond the target alloy composition is removed while simultaneously creating a porous structure. Further integration with annealing allows for the uniform diffusion of zinc and the formation of a copper-zinc alloy, while preserving the porous structure. This solves the problems of complex processes for creating porous structures and uneven alloying element composition in existing technologies.

[0019] 3. Process versatility: This method is simple and efficient, with controllable composition, strong repeatability of experimental results, and low equipment requirements. It is suitable for the mass production of self-supporting micro / nano porous copper-zinc alloys. It not only provides a simple way for the preparation and morphology control of porous copper-zinc alloys, but can also be extended to the preparation of other alloy materials, further promoting the development of new materials and devices.

[0020] 4. Excellent Performance: The porous copper-zinc alloy current collector obtained by this method has a pore structure of 1-3 μm and a single-phase Cu3Zn. The porous copper-zinc alloy current collector is bendable, meeting the mechanical strength requirements for use as an electrode. The unique porous structure of this current collector, combined with the alloy composition, synergistically enhances the electrochemical performance of the battery. The constructed half-cell operates at 4 mA cm⁻¹. -2 The cell maintained a stable coulombic efficiency of approximately 99.7% after 10,000 cycles at a stable current density; the assembled full cell still maintained a capacity of 182.2 mAh g⁻¹ after 2,000 cycles. -1 Its high specific capacity and capacity retention of up to 94.6% fully demonstrate its excellent electrochemical reversibility and long-term cycling stability. Attached Figure Description

[0021] Figure 1 This is the X-ray diffraction pattern of untreated H62 brass in Example 1 of the present invention.

[0022] Figure 2 The X-ray diffraction pattern of the porous copper-zinc alloy current collector obtained after annealing treatment in Example 1 of the present invention is shown.

[0023] Figure 3 The X-ray diffraction pattern of the porous copper current collector obtained after vapor-phase dealloying in Comparative Example 1 of this invention is shown.

[0024] Figure 4 This is a macroscopic photograph of commercial brass foil H62 from Embodiment 1 of the present invention.

[0025] Figure 5 This is a macroscopic photograph of the porous copper-zinc alloy current collector obtained after annealing treatment in Example 1 of the present invention.

[0026] Figure 6 This is a macroscopic photograph of the porous copper current collector obtained after vapor-phase dealloying in Comparative Example 1 of this invention.

[0027] Figure 7 The X-ray photoelectron spectra of the porous copper-zinc alloy current collector obtained after annealing in Example 1 of the present invention and the porous copper current collector obtained after vapor-phase dealloying in Comparative Example 1 are shown.

[0028] Figure 8 The image shows the energy-dispersive X-ray spectroscopy characterization obtained by taking five nearly equidistant points in the vertical direction of the cross-section of the current collector obtained in Example 1 and Comparative Example 1.

[0029] Figure 9 This is a scanning electron microscope image of the surface of H62 brass foil.

[0030] Figure 10 This is a scanning electron microscope (SEM) image of the porous copper-zinc alloy current collector obtained after annealing treatment in Example 1 of the present invention.

[0031] Figure 11 This is a scanning electron microscope (SEM) image of the porous copper current collector obtained after vapor-phase dealloying in Comparative Example 1 of this invention.

[0032] Figure 12 The diagram shows the coulombic efficiency of the porous copper-zinc alloy current collector and the half-cell assembled with zinc after annealing treatment in Example 1 of this invention.

[0033] Figure 13 The diagram shows the coulombic efficiency of the half-cell assembled with zinc using the porous copper current collector obtained after vapor-phase dealloying in Comparative Example 1 of this invention.

[0034] Figure 14 The diagram shows the coulombic efficiency of the porous copper-zinc alloy current collector obtained after annealing treatment in Comparative Example 2 of this invention, and the half-cell assembled with zinc.

[0035] Figure 15 A full cell assembled with a porous copper-zinc alloy current collector and a positive electrode using pre-deposited zinc in 1A g -1 Cyclic stability plot at current density. Detailed Implementation

[0036] The present invention will be further described below with reference to specific embodiments. The following description is for illustrative purposes only and does not limit the scope of the invention. Unless otherwise specified, all percentages of metals described below are by mass.

[0037] Example 1 (1) The surface of H62 brass foil with a thickness of 50 μm was ultrasonically cleaned by deionized water and anhydrous ethanol in sequence, and the cleaned brass foil was vacuum dried.

[0038] (2) Place the brass foil into the quartz tube of the vacuum tube furnace and evacuate the tube furnace until the vacuum level is below 10 Pa, then close the vacuum valve.

[0039] (3) Open the inlet valve of the tubular furnace and introduce a mixture of argon and hydrogen with a hydrogen content of 7 vol.% into the tubular furnace. After the gas pressure in the tube is slightly higher than the normal atmospheric pressure, close the inlet valve and open the vacuum valve and vacuum pump again to further extract the residual air in the tube and reduce the vacuum to below 10 Pa.

[0040] (4) Repeat (3) twice until the furnace pressure is lower than 10 Pa. Then, adjust the gas flow rate through the gas inlet valve and introduce a mixture of argon and hydrogen with a hydrogen content of 7 vol.% to maintain the furnace pressure at 200 Pa.

[0041] (5) With gas flow ensured and no air enters, start the tube furnace for vapor phase dealloying treatment, raise the temperature to 650 ℃ at a heating rate of 10 ℃ / min and hold for 20 min. After holding, keep the gas flow open and cool down.

[0042] (6) After the temperature inside the tube drops to room temperature, close the vacuum valve and vacuum pump, and continuously introduce a mixture of argon and hydrogen gas. When the gas pressure inside the tube is higher than the normal atmospheric pressure, connect the gas pipe at the outlet valve end to the water tank and open the outlet valve to make the gas pressure inside the tube consistent with the normal atmospheric pressure.

[0043] (7) Under conditions where the mixed gas of argon and hydrogen flows freely and no air enters, start the tube furnace for annealing treatment, heating to 600 ℃ at a heating rate of 10 ℃ / min and holding for 60 min. After the holding period, cool to room temperature to obtain a porous copper-zinc alloy current collector. The copper:zinc ratio of the porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0044] Example 2 (1) The surface of H65 brass foil with a thickness of 50 μm was ultrasonically cleaned by using deionized water and anhydrous ethanol in sequence, and the cleaned brass foil was vacuum dried.

[0045] (2) Same as Example 1.

[0046] (3) Same as Example 1.

[0047] (4) Same as Example 1.

[0048] (5) With gas flow ensured and no air enters, start the tube furnace for vapor phase dealloying treatment, raise the temperature to 650 ℃ at a heating rate of 10 ℃ / min and hold for 15 min. After holding, keep the gas flow open and cool down.

[0049] (6) Same as Example 1.

[0050] (7) Under conditions where the mixed gas of argon and hydrogen flows freely and no air enters, start the tube furnace for annealing treatment, heating to 600 ℃ at a heating rate of 10 ℃ / min and holding for 45 min. After the holding period, cool to room temperature to obtain a porous copper-zinc alloy current collector. The copper:zinc ratio of the porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0051] Example 3 (1) The surface of H70 brass foil with a thickness of 50 μm was ultrasonically cleaned by using deionized water and anhydrous ethanol in sequence, and the cleaned brass foil was vacuum dried.

[0052] (2) Same as Example 1.

[0053] (3) Same as Example 1.

[0054] (4) Same as Example 1.

[0055] (5) With gas flow ensured and no air enters, start the tube furnace for vapor phase dealloying treatment, raise the temperature to 650 ℃ at a heating rate of 10 ℃ / min and hold for 8 min. After holding, keep the gas flow open and cool down.

[0056] (6) Same as Example 1.

[0057] (7) Under conditions where the mixed gas of argon and hydrogen flows freely and no air enters, start the tube furnace for annealing treatment, heating to 600 ℃ at a heating rate of 10 ℃ / min and holding for 25 min. After the holding period, cool to room temperature to obtain a porous copper-zinc alloy current collector. The copper:zinc ratio of the porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0058] Example 4 Compared with Example 1, except that the thickness of the brass foil in step (1) is 10 μm, the dealloying time in step (5) is 2 min, and the holding time for annealing in step (7) is 30 min, the rest is the same as Example 1. The copper:zinc ratio of the obtained porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0059] Example 5 Compared with Example 1, except that the thickness of the brass foil in step (1) is 150 μm and the dealloying time in step (5) is 50 min, the rest is the same as Example 1. The obtained porous copper-zinc alloy current collector has a copper:zinc ratio of 3:1 (atomic ratio) and a pore size of 1-2 μm.

[0060] Example 6 Compared with Example 1, except that the thickness of the brass foil in step (1) is 1000 μm, the dealloying time in step (5) is 320 min, and the holding time for annealing in step (7) is 360 min, the rest is the same as Example 1. The obtained porous copper-zinc alloy current collector has a copper:zinc ratio of 3:1 (atomic ratio) and a pore size of 1-3 μm.

[0061] Example 7 Compared with Example 1, except that the furnace pressure in step (4) is 100 Pa and the dealloying time in step (5) is 15 min, the rest is the same as Example 1. The copper:zinc ratio of the obtained porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0062] Example 8 Compared with Example 1, except that the dealloying temperature in step (5) is 600 ℃ and the dealloying time is 25 min, the rest is the same as Example 1. The copper:zinc ratio of the obtained porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0063] Example 9 Compared with Example 1, except that the dealloying temperature in step (5) is 700 ℃ and the dealloying time is 15 min, the rest is the same as Example 1. The copper:zinc ratio of the obtained porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0064] Example 10 Compared with Example 1, except that the holding temperature of the annealing treatment in step (7) is 550 ℃ and the holding time is 80 min, the rest is the same as Example 1. The copper:zinc ratio of the obtained porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0065] Example 11 Compared with Example 1, except that the holding temperature of the annealing treatment in step (7) is 650 ℃ and the holding time is 40 min, the rest is the same as Example 1. The copper:zinc ratio of the obtained porous copper-zinc alloy current collector is 3:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0066] Comparative Example 1 Compared with Example 1, step (7) is omitted, and no annealing is performed after the dealloying treatment. The resulting product is a porous copper current collector. The copper:zinc ratio in the porous copper current collector is 8:1 (atomic ratio), and the pore size is 1-3 μm.

[0067] Comparative Example 2 Compared with Example 1, except that the dealloying temperature in step (5) is 750 ℃ ​​and the dealloying time is 20 min, the rest is the same as Example 1. The copper:zinc ratio of the obtained porous copper-zinc alloy current collector is 4:1 (atomic ratio), and the pore size is 1-1.5 μm.

[0068] Performance verification 1. X-ray diffraction analysis was performed on the H62 brass foil, the porous copper-zinc alloy current collector obtained in Example 1, and the porous copper current collector obtained in Comparative Example 1. The X-ray diffraction pattern of the H62 brass foil is shown below. Figure 1 As shown, the X-ray diffraction pattern of the porous copper-zinc alloy current collector in Example 1 is as follows. Figure 2 As shown, the X-ray diffraction pattern of the porous copper current collector obtained in Comparative Example 1 is as follows. Figure 3 As shown. Macroscopic photographs of H62 brass foil, the current collector obtained in Example 1, and the current collector obtained in Comparative Example 1 are shown. Figure 4-6 As shown in the figure. It can be seen from the figure that after vapor-phase dealloying, the phase of the current collector changes from Cu... 0.64 Zn 0.36 The alloy phase transforms into the Cu phase, and the color changes from yellowish-brown to brick red. Further annealing transforms the phase into a Cu3Zn alloy phase, with the corresponding color becoming bright yellow. This demonstrates that the annealing process successfully alloys copper and zinc.

[0069] The current collectors obtained in Examples 2-11 were subjected to X-ray diffraction analysis, and the X-ray diffraction patterns were similar to those in Example 1.

[0070] 2. X-ray photoelectron spectroscopy characterization was performed on the current collectors obtained in Example 1 and Comparative Example 1. The results are as follows: Figure 7 As shown in the figure, the elemental ratio of copper to zinc on the surface of the current collector changed from 8:1 in Comparative Example 1 to 3:1 in Example 1. Furthermore, energy-dispersive X-ray spectroscopy characterization was performed on five nearly equidistant points taken vertically from the cross-sections of the current collectors obtained in Example 1 and Comparative Example 1. The results are shown in the figure. Figure 8 As shown in the figure, the porous copper current collector of Comparative Example 1 exhibits a clear compositional gradient in copper and zinc content, with the zinc content increasing from the surface to the interior. In contrast, the copper and zinc content in the porous copper-zinc alloy current collector of Example 1 remains nearly constant at all test points and is close to the stoichiometric values ​​of the Cu3Zn phase. This indicates that the annealing treatment achieved uniform diffusion of zinc.

[0071] 3. Scanning electron microscope (SEM) images of the surface of the H62 brass foil, the current collectors obtained in Example 1 and Comparative Example 1 are shown below. Figure 9-11 As shown in the figure, after dealloying, the resulting current collector achieves a porous structure. The current collector after annealing retains a similar porous structure.

[0072] Application examples 1. The porous copper-zinc alloy current collectors obtained in Example 1, Comparative Example 1, and Comparative Example 2 were respectively punched into discs with a diameter of 12 mm. Using either the porous copper-zinc alloy current collector or the porous copper current collector as the working electrode, a zinc sheet as the counter electrode and reference electrode, glass fiber as the separator, and 2 M ZnSO4 aqueous solution as the electrolyte, they were assembled into a button-type half-cell in the following order: positive electrode shell - porous copper-zinc alloy current collector or porous copper current collector - separator with added electrolyte - zinc sheet - gasket - spring - negative electrode shell. The button-type half-cell was heated to 4 mA cm⁻¹. -2 Current density, 0.5 mAh cm⁻¹ -2 Electrochemical performance tests were conducted under a fixed cycle specific capacity to assess the stability of zinc deposition and stripping in the porous copper-zinc alloy current collector and the porous copper current collector, respectively. The coulombic efficiency of the half-cell assembled with the porous copper-zinc alloy negative electrode current collector in Example 1 is shown in [reference needed]. Figure 12 The coulombic efficiency of the half-cell assembled with the porous copper negative electrode current collector in Comparative Example 1 is shown in [reference needed]. Figure 13 The coulombic efficiency of the half-cell assembled with the porous copper-zinc alloy negative electrode current collector in Comparative Example 2 is shown in [reference needed]. Figure 14As can be seen from the figure, the half-cell assembled with the porous copper-zinc alloy current collector in Example 1 operates at 4 mA cm⁻¹. -2 The porous copper-zinc alloy current collector maintained approximately 99.7% coulombic efficiency after 10,000 cycles at a low current density, demonstrating excellent stability as a zinc metal carrier under low current densities. In contrast, the coulombic efficiency of the half-cell assembled with the porous copper current collector in Comparative Example 1 fluctuated more dramatically, experiencing a severe spike after 1958 cycles. This strong contrast in coulombic efficiency stability between Example 1 and Comparative Example 1 highlights the advantages of the annealed homogeneous alloy phase obtained in this invention as a zinc metal carrier. Although Comparative Example 2 also underwent annealing, its coulombic efficiency fluctuation was relatively stable, but a severe spike also occurred after 4474 cycles, indicating that other homogeneous alloy phases still suffer from insufficient stability during long-term cycling. This further verifies the significant superiority of the Cu3Zn phase selected in this invention as a zinc metal carrier.

[0073] The porous copper-zinc alloy current collectors prepared in Examples 2-11 were assembled into half-cells using the same method described above, and their electrochemical performance was tested in the same manner. The results showed that at 4 mA cm⁻¹, the performance was good. -2 Current density, 0.5 mAh cm⁻¹ -2 Under the condition of fixed cycle specific capacity, the half-cell assembled with porous copper-zinc alloy current collectors in Examples 2-11 also maintained a high coulombic efficiency of over 98% after 10,000 cycles.

[0074] 2. The porous copper-zinc alloy current collector obtained in Example 1 is punched into a circular piece with a diameter of 12 mm, and assembled into a half-cell according to the method in step 1 above. Then, it is charged with 4 mA cm⁻¹ -2 The current density was pre-deposited on a porous copper-zinc alloy current collector at 4 mAh / cm². -2 Zinc metal was used as the negative electrode. Zinc vanadate (ZVO), carbon black, and polyvinylidene fluoride were mixed in N-methylpyrrolidone at a mass ratio of 8:1:1 to form a slurry. The slurry was coated onto carbon paper and dried under vacuum to obtain the positive electrode. A full cell was assembled using glass fiber as the separator and 3 M Zn(OTF)₂ aqueous solution as the electrolyte, following the assembly method of positive electrode shell-positive electrode-separator with added electrolyte-pre-deposited zinc porous copper-zinc alloy current collector or porous copper current collector-gasket-spring sheet-negative electrode shell. -1 Cycling was performed within a current density and a voltage range of 0.2 to 1.6 V. Figure 15 A full cell assembled with a porous copper-zinc alloy current collector and cathode (ZVO) for pre-deposited zinc was used in a 1A g... -1The figure shows the cycling stability at current density. As can be seen from the figure, the porous copper-zinc alloy current collector of this invention still exhibits a high specific capacity (182.2 mAh g⁻¹) after 2000 cycles in a full cell. -1 It also boasts excellent cycle stability (capacity retention of up to 94.6%).

Claims

1. A method for preparing a porous copper-zinc alloy current collector, characterized in that: Includes the following steps: (1) Clean the surface of the brass foil and then vacuum dry it; (2) Place the dried brass foil into a vacuum tube furnace and evacuate it; (3) Introduce a mixture of hydrogen and inert gas into the vacuum tube furnace, then evacuate the vacuum, repeating this process at least once to further remove residual air from the tube. (4) A mixture of hydrogen and inert gas is continuously introduced into the vacuum tube furnace and the furnace is kept at a low pressure. The temperature is raised to carry out vapor phase dealloying treatment. After the treatment is completed, the temperature is lowered to room temperature. (5) Without air entering, a mixture of hydrogen and inert gas is introduced into the vacuum tube furnace until the pressure inside the furnace is atmospheric pressure. Then, the temperature is raised for annealing. After annealing, the temperature is lowered to room temperature to obtain a porous copper-zinc alloy current collector.

2. The preparation method according to claim 1, characterized in that: In step (1), the brass foil has a copper mass fraction of 60-70%, a zinc mass fraction of 30-40%, and a thickness of 10-1000 μm.

3. The preparation method according to claim 1, characterized in that: In step (2), vacuuming is performed to ensure that the pressure inside the furnace is below 10 Pa.

4. The preparation method according to claim 1, characterized in that: In steps (3)-(5), the volume fraction of hydrogen in the mixture of hydrogen and inert gas is 5-10%.

5. The preparation method according to claim 1, characterized in that: In step (3), vacuuming is performed to ensure that the pressure inside the furnace is below 10 Pa; the operation of introducing a mixture of hydrogen and inert gas and vacuuming is repeated 1-3 times.

6. The preparation method according to claim 1, characterized in that: In step (4), the low-pressure state refers to the gas pressure inside the furnace being between 100 and 200 Pa.

7. The preparation method according to claim 1 or 6, characterized in that: In step (4), the heating rate is set to 8-11 ℃ / min, the vapor phase dealloying temperature is set to 600-700 ℃, and the holding time is set to 2~320min.

8. The preparation method according to claim 1, characterized in that: In step (5), during the annealing process, the heating rate is set to 8-11 ℃ / min, the annealing temperature is set to 550-650 ℃, and the holding time is set to 25~360 min.

9. A porous copper-zinc alloy current collector prepared according to any one of claims 1-8; preferably, the atomic ratio of copper to zinc in the porous copper-zinc alloy current collector is 3:1, and the pore size is 1-3 μm.

10. The application of the porous copper-zinc alloy current collector according to claim 9 in a zinc-ion battery; preferably, the zinc-ion battery is an aqueous zinc-ion battery.